Corruption and Infrastructural Decay: Perceptible Evidence from Nigeria - Effiom, Lionel (2014)
Globally, evidences abound in literature confirming a strong nexus between corruption and infrastructural decay. This paper attempts to articulate descriptively the link between corruption and infrastructural decay in Nigeria. Two selected infrastructural sub-sectors (electricity and governance) were briefly examined and used to demonstrate the correlation between corruption and the current state of infrastructural decay. It was very glaring from the simple correlation analysis that it is not absolute lack of funds that has caused infrastructural decay but outright mismanagement of funds (corruption) that is principally responsible for the level of infrastructural decay in Nigeria. On the basis of this analysis, some policy options were suggested. In essence, the promotion and institutionalization of good governance, long term infrastructural planning and public private partnership in the provision of infrastructures were among the policies recommended. Key words: Corruption, infrastructure, decay, governance and Nigeria